PELAKSANAAN UPACARA ADAT PERKAWINAN DAYAK CUPANGK DESA DI DESA KUNYIL KECAMATAN MELIAU KABUPATEN SANGGAU - NIM. A1012191137, TIARA ESA KINANTI (Jurnal Fatwa Hukum, 2025)
Abstract  The Dayak Cupangk community in Kunyil Village is guided by applicable customary laws, one of which is marriage customs which are still adhered to and implemented to this day. Marriage customs are one of the ancestral traditions that are still carried out from generation to generation. However, as time went by, the Cupangk Dayak people in Kunyil Village, Meliau District, Sanggau Regency did not carry out traditional marriages according to their original customs. The formulation of the research problem is "Are the traditional marriage ceremonies of the Dayak Cupangk community in Kunyil Village, Meliau District, Sanggau Regency, carried out according to original customs?"The type of research is carried out using empirical research methods, with a type of approach using a descriptive analysis approach, namely providing a careful description of a situation or symptom of the object of this research, with the aim of solving problems based on the facts collected.So it is concluded that the implementation of traditional marriage ceremonies in the Dayak Cupangk community in Kunyil Village has experienced a shift so that the implementation is more simplified, such as the implementation and completeness are more simplified; that the factors that cause a shift in the implementation of traditional marriage ceremonies in the Dayak Cupangk community of Kunyil Village are due to economic factors, religious factors and the difficulty of fittings for wedding ceremonies and customs due to economic factors, religious factors and the difficulty of finding traditional wedding ceremony fittings, that the consequences of Dayak Cupangk law Villagers who violate customs related to not carrying out traditional marriage ceremonies are subject to violating the customs of one half of three amas in the form of goods or objects that have been determined or can also be converted into rupiah by paying a customary fine according to the value that has been determined. determined and that the legal efforts undertaken by traditional functionaries in preserving the customary marriage laws of the Dayak Cupangk community in Kunyil Village, Meliau District, Sanggau Regency are by holding deliberations with the Kunyil Village community so that they can become role models for future generations.Keywords: Law, Custom, Marriage  Abstrak  Masyarakat Dayak Cupangk Di Desa Kunyil bepedoman pada hukum adat yang berlaku salah salah satunya adalah adat perkawinan yang sampai saat ini masih ditaati dan dilaksanakan. Adat perkawinan merupakan salah satu adat warisan leluhur yang sampai saat ini masih dilakukan secara turun temurun. Namun seiring berjalannya waktu masyarakat Dayak Cupangk Di Desa Kunyil Kecamatan Meliau Kabupaten Sanggau tidak melaksanakan perkawinan adat sesuai adat aslinya. Adapun rumusan masalah penelitian ini adalah " Apakah Upacara Adat Perkawinan Masyarakat Dayak Cupangk di Desa Kunyil Kecamatan Meliau Kabupaten Sanggau Dilaksanakan Sesuai Adat Aslinya"Adapun jenis penelitian dilakukan dengan menggunakan metode penelitian empiris, dengan jenis pendekatan menggunakan pendekatan deskriptif analisis, yaitu memberikan gambaran secara cermat mengenai sesuatu keadaan atau gejala objek penelitian ini, dengan maksud untuk memecahkan permasalahan berdasarkan fakta-fakta yang terkumpul .Maka menyimpulkan bahwa pelaksanaan upacara adat perkawinan pada masyarakat Dayak Cupangk Di Desa Kunyil mengalami pergeseran sehingga pelaksanaannya lebih disederhanakan seperti pelaksanaan dan kelengkapanny yang lebih disederhanakan; bahwa faktor yang menyebabkan terjadinya pergeseran pelaksanaannya upacara adat perkawinan pada masyarakat Dayak Cupangk di Desa kunyil dikarenakan faktor Ekonomi, faktor agama dan sulitnya alat kelengkapan upacara dan adat perkawinan dikarenakan faktor ekonomi , faktor   agama dan sulitnya alat kelengkapan upacara adat perkawinan ditemukan, bahwa akibat hukum Dayak Cupangk di Desa Kunyil bagi pelanggar adat terkait dengan tidak dilaksanakannya upacara adat perkawinan dikenakan melanggar adat setongah tiga amas berupa bisa dalam bentuk barang atau benda yang sudah ditentukan atau dapat juga dirupiahkan dengan membayar denda adat sesuai dengan nilai yang sudah ditentukan dan bahwa upaya hukum yang dilakukan oleh fungsionaris adat dalam melestarikan hukum adat perkawinan masyarakat Dayak Cupangk Di Desa Kunyil Kecamatan Meliau Kabupaten Sanggau adalah dengan melakukan musyawarah bersama masyarakat Desa Kunyil agar dapat menjadi teladan bagi generasi-generasi penerus selanjutnyaKata Kunci : Hukum, Adat, Perkawinan